The Process of Proving Evidence of Electronic Certificates of Land Rights in Civil Cases Trials at the District Court - Rehabeam Mofu (PT FORMOSA CENDEKIA GLOBAL, 2023)
The legal procedures for proving electronic certificates of land rights in district courts have not yet been regulated in Law number 11 of 2008 concerning Electronic Information and Transactions or the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 1 of 2021 concerning Electronic Certificates. However, the rules do not yet exist. However, suppose later there is a case. In that case, the judge must still accept the case to be tried and decided, based on the assumption that the judge is considered to know the Law (ius curia novit) in order to achieve a simple, fast, and low-cost trial by applying the use of electronic certificates land rights as a reserve. At the same time, the primary evidence is a physical certificate of land rights. However, suppose it is used as the primary evidence. In that case, the proof method is by opening the electronic document data together before the litigants using a computer device connected to the internet in Court during the evidentiary event. The evidentiary strength of the electronic certificate of land rights as evidence at the Class IA Jayapura District Court trial is the same as the physical certificate of land rights, namely having the strength of physical, formal, and material evidence. The Government immediately issues procedural law rules in proving related to electronic certificates so that there is no legal vacuum.